DESAIN SISTEM: VISUAL BASIC FOR APPLICATION EXCEL 2010 UNTUK PENGGAJIAN GURU MADRASAH ALIYAH MUHAMMADIYAH I MALANG - Ahmad Bukhori S (LP3M IAI Al-Qolam, 2019)
In the world of education in Indonesia, computers have been introduced and used in schools ranging from basic education to tertiary institutions. Computers make it easy to find and provide learning materials can also be obtained, for example by the concept of electronic libraries (e-libraries) or electronic books (e-books). MA Muhammadiyah I Malang is a school that is equivalent to a high school (SMA) that has used a computer as a tool for the process of teaching and learning activities, finance, administration and so forth. Computers are tools that help humans in making reports or in producing information that can be achieved as a basis for decision making and can contribute more to data storage and data retrieval processes. Currently in the financial section for the processing of teaching fees and employee honorariums still use Microsoft Excel. Separate financial data in several sheets that require separate data input for each sheet so that financial calculations and reporting are less efficient and fast. The bookkeeping process is sometimes very difficult, complicated or even troublesome for some people. But today's computer technology has been able to change this process to be easier, simpler, faster and more efficientPayroll system is a computer application created to make it easier for employees in the financial department to make, calculate, report and analyze school financial turnover so that the application can provide optimal services to teachers and employees as a support for timely decision making.